URGENSI PENGAWASAN EKSTERNAL HAKIM MAHKAMAH KONSTITUSI DALAM PENGUJIAN UNDANG-UNDANG BERDASARKAN KEKUASAAN KEHAKIMAN MENURUT UUD NRI 1945 - Sibarani, Mery R.L; Hutahean, Armunanto (Honeste Vivere, 2024)
This research discusses the urgency of external supervision of Constitutional Court judges in reviewing laws from the perspective of judicial power. The research uses normative juridical methods. The aim of the research is to examine the urgency of external supervision of constitutional court judges in reviewing laws and supervision of Constitutional Court Judges according to the judicial powers in the 1945 Constitution of the Republic of Indonesia. The results of this research find that external supervision of Constitutional Court Judges is an important thing to go along with supervision which takes place internally, namely the Ethics Council of the Constitutional Court and the Honorary Council of the Constitutional Court (MKMK). As for external supervision of Constitutional Court Judges, it does not violate the principles of judicial power and the independence of judges and the impartiality of judges because its application is carried out in enforcing the code of ethics of behavior of Constitutional Judges and the aim of judicial power to enforce law and justice. Furthermore, the authorized institution is the Judicial Commission (KY) because it is a constitutional organ and its implementation must amend the 1945 Constitution of the Republic of Indonesia to explicitly explain the supervisory function of the KY in the Supreme Court and Constitutional Court. Apart from that, the absence of external supervision as a check & balance for the Constitutional Court against the Constitutional Court is due to Constitutional Court Decision No. 005/PUU-XII/2006 and PMK No. 1-2/PUU-XII/2014. This is because in this decision the Constitutional Court judges were excluded from the authority of the KY because the decision was different from the interpretation of the Supreme Court judges